2012
DOI: 10.1016/j.joca.2012.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Icariin: a potential promoting compound for cartilage tissue engineering

Abstract: Icariin can be a potential promoting compound for cartilage tissue engineering, and it can be a substitute for the use of some growth factors. The long history and extensive cases of safe use in China, Japan and Korea make it more attractive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 30 publications
3
67
0
1
Order By: Relevance
“…[22][23][24] Furthermore, rapid degradation, easily lost activity, and the high cost of growth factors limit their widespread use, particularly in clinical practices. [25][26][27] The ASUs are natural vegetable extracts made up of avocado and soybean oils in a proportion of one-third to two-thirds. 28 In a study, Gabay et al reported that avocado/soybean reduce the activity of the transcription factor nuclear factor-κB in an inflammatory model induced by tumor necrosis factor-α and protect chondrocytes from damage due to osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] Furthermore, rapid degradation, easily lost activity, and the high cost of growth factors limit their widespread use, particularly in clinical practices. [25][26][27] The ASUs are natural vegetable extracts made up of avocado and soybean oils in a proportion of one-third to two-thirds. 28 In a study, Gabay et al reported that avocado/soybean reduce the activity of the transcription factor nuclear factor-κB in an inflammatory model induced by tumor necrosis factor-α and protect chondrocytes from damage due to osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…When rabbit chondrocytes isolated from articular cartilage were cultured in vitro with different concentrations of icariin, the higher concentration of icariin produced more extracellular matrix synthesis and expression of chondrogenesis genes of chondrocytes (Zhang et al ., ). The effect of icariin on the synthesis of glycosaminoglycans (GAGs) and collagen of chondrocytes, and its potent chondrogenic effect, might be due to its ability to up‐regulate the expression of aggrecan, collagen II, and Sox9 genes and to down‐regulate the expression of the collagen I gene of chondrocytes (Li et al ., ). It also improves the efficiency of restoring of supercritical‐sized osteochondral defects in adult rabbit model and enhances the integration of newly formed cartilage with subchondral bone (Li et al ., ).…”
Section: Underlying Mechanisms Of Icariin For Bone Regenerationmentioning
confidence: 99%
“…The effect of icariin on the synthesis of glycosaminoglycans (GAGs) and collagen of chondrocytes, and its potent chondrogenic effect, might be due to its ability to up‐regulate the expression of aggrecan, collagen II, and Sox9 genes and to down‐regulate the expression of the collagen I gene of chondrocytes (Li et al ., ). It also improves the efficiency of restoring of supercritical‐sized osteochondral defects in adult rabbit model and enhances the integration of newly formed cartilage with subchondral bone (Li et al ., ). These preliminary studies imply that icariin might be an effective accelerant for chondrogenesis and a substitute for the use of some growth factors.…”
Section: Underlying Mechanisms Of Icariin For Bone Regenerationmentioning
confidence: 99%
“…일반적으로 재활치료를 포함한 약물 치료 및 수술적인 방법이 시행되고 있으나, 만성적이고 진행성인 질 환의 특성상 통증 조절이나 관리가 어려운 실정이다. 최근에 는 관절염에 대한 효과적인 치료법 및 발병기전 등에 대한 연 구가 발전되면서 연골의 파괴를 억제하고 질병의 진행을 예방 하기 위한 새로운 천연약물 소재의 개발이 활발하게 이루어지 고 있다 (Altman, 2008;Alaaeddine et al, 2012;Li et al, 2012;Huh et al, 2012). MeOH (25 : 1 → 1 : 2) 혼합용매를 사용하여 기울기 용리하여 최종 acetylshikonin (1.1 g)을 분리, 정제하였다.…”
Section: 있다 최근 지치의 생육시기별 시코닌 색소 함량 및 항산화 활성에 대해 보고되기도 하였다unclassified